Traces of faith in the lives of young Christians - Guritno, Maria Priskila Noya; Witaningsih, Agustina Kurnia; Wijayanti, Lucia Wiwid (Proceedings of International Conference on Research in Education, 2025)
Young Christians are called to follow the path of faith amidst the challenges of our time, such as digitalization, secularization, and the search for identity. In Christus Vivit, Pope Francis affirms that the living Christ is present with young people, guiding them to discover the true meaning of life in the light of the Gospel. Therefore, young people's path of faith needs to be nurtured so that they can bear witness to Christ's love in their daily lives. This paper was compiled using a document review method. The Apostolic Exhortation Christus Vivit issued by Pope Francis was the primary source evaluated. After reading and examining the document's contents, the author summarizes the key points. Christus Vivit affirms that young people are a vital part of the Church, called to walk the path of faith joyfully amidst the challenges of the modern age. This document serves as a relevant guide for young Christians to draw closer to the living Christ. Therefore, it is important for young people to internalize this message through active involvement in the life of the Church, while families and pastoral care providers are expected to support their continued growth in faith.
Keywords: Christus Vivit; Church; faith; spirituality; young Christians